AN IMAGE PROCESSING BASED AUTOMATED CAR PARKING SYSTEM (International Journal of Food and Nutritional Sciences, 2023)
In this work, posit an Internet - of - things intelligent parking mechanism that can provide park and ride allotment guidance to clients as well as monitor and book the vehicle's parking spot. We used a deep learning algorithm technique to identify the registration plate accessing the parking space entrance using a PI camera. In this system, the output of the IP camera will be processed using image processing techniques. The system will automatically register the vehicle using a number plate value and stores data with the server. Then the system can monitor each parking slot's status by installing an IR sensor on the slot. Accordingly, sensors detect parking slot availability and send status to ESP32. It gathers data among all sensing devices and transmits it to the cloud service. This allows users to check the parking availability from anywhere using the internet and any browser. The mobile application users can find and book a parking slot in advance.